Immunohistochemical characteristics of basal-like breast cancer - Badowska-Kozakiewicz, Anna; Budzik, Michał (Contemporary Oncology/Współczesna Onkologia, 2016)
Basal-like breast cancer (BLBC) occurs mainly in young patients. It is characterized by an aggressive clinical outcome, presence of distant metastases, particularly within the first five years of the disease, bad prognosis and relatively high mortality. Recently greater interest of scientists in this subtype of breast cancer has been observed. Despite such many well-known potential biomarkers of BLBC, currently there is no official international panel of antigens dedicated to diagnosis of this subtype of breast cancer. The most commonly used set in this case contains four antibodies – estrogen receptor (ER), epidermal growth factor receptor (EGFR) and human epidermal growth factor receptor 2 (HER2) and cytokeratins (CK) 5/6 – although it cannot provide one hundred percent detectability of these lesions. Incorporation of additional biomarkers into a panel can increase specificity, at the potential cost of sensitivity. Many biomarkers have been associated with the basal-like phenotype, and those with high sensitivity and/or specificity could improve the performance of immunohistochemical surrogate panels. Work on detection of the best of them is constantly being performed.